Can central banks boost corporate investment: Evidence from the ECB liquidity injections - Stine Louise Daetz; Marti G. Subrahmanyam; Dragon Yongjun Tang; Sarah Qian Wang (Danmarks Nationalbank, 2018)
Can monetary stimulus boost corporate investment? We answer this question by studying ECB's 2011-2012 Longer-Term Refinancing Operations (LTROs), which provided cheap funding to Eurozone banks. We find that, relative to their non-Eurozone counterparts, Eurozone firms invested more after the LTROs. However, riskier banks took more funds from the LTROs, and their uptake is negatively associated with their clients' investment. In other words, firms reduced investment when their banks took cheap LTRO funds from the ECB. Overall, our results highlight the difficulty of boosting investment by injecting liquidity into the banking system, especially with impaired bank balance sheets.
Keywords: G32; G38; 330; Unconventional Monetary Policy; ECB Interventions; Corporate Policies; Real Economy